Competency requirements for patients and therapists in telerehabilitation aftercare: a qualitative study - Stark-Blomeier, Anna Lea; Krayter, Stephan; Dockweiler, Christoph (Frontiers in Rehabilitation Sciences, 2025)
IntroductionRehabilitation aftercare serves to maintain the success of treatment following medical rehabilitation. Digital services, such as app-based training or therapist-led video calls, are increasingly being used in rehabilitation and aftercare as alternatives that are more flexible in terms of space and time. However, such systems place various demands on users. The study aims to identify the requirements and competencies needed by patients and therapists for the successful use of telerehabilitation aftercare in Germany.Materials and methodsThe study employed an explorative, qualitative approach. Focused interviews were conducted to gather user experiences with telerehabilitation aftercare. Fifteen therapists participated in three focus group interviews, while five patients took part in three individual or two-person interviews. Using an interview guideline, patients and therapists were asked about steps, preparation processes, required competencies and adaptation possibilities in relation to telerehabilitation aftercare. The evaluation was carried out using structuring content analysis according to Kuckartz and Rädiker.ResultsDepending on the program used and the professional background of the therapists, the perceived usage requirements differed, including technical handling, motivation for training and individual therapy adaptations. Both target groups considered application-, process- and impact-related knowledge, technical, social-emotional and cognitive skills, a positive attitude towards technology and technical experience as necessary. Therapists emphasized professional skills as well as experience, and patients sufficient physical skills such as motor skills. The influence of socio-demographic factors on usage was controversially discussed.ConclusionFindings suggest to focus not only on technical but also on professional and social competencies in training and further education in order to promote the competent use of telerehabilitation aftercare. If sufficient opportunities are created to get to know and try out such programs, uncertainties could be reduced and positive user experiences can be promoted. Due to the small sample size, the results cannot be generalized without restriction, and further research with a larger and more diverse sample is necessary.